Cardilopin effectiveness in cardiohemodynamics correction among scoliosis patients - R. V. Enaldieva; A. G. Avtandilov; S. T. Vetrile; A. A. Kuleshov; G. Ch. Makhakova; I. A. Krutovtsev; I. V. Velitchenko (Российский кардиологический журнал)
The article is devoted to prolonged calcium antagonist, Cardilopin, effectiveness in patients with severe thoracic scoliosis, complicated by pulmonary hypertension and right ventricular diastolic dysfunction (RVDD). The study involved 43 patients aged 18-39, with Stage TV scoliosis diagnosed in childhood. According to Doppler echocardiography data,24 participants had pulmonary hypertension, RV hypertrophy and dilatation, Type 1 RVDD. These patients received Cardilopin (amplodipine, Egis, Hungary),5mg/d, for 12 weeks. Monthly control of pulmonary artery blood pressure (PA BP) demonstrated that the tendency towards mean PABP decrease manifested as early as by the end of the first month, lasting till the end of the study. Moreover, RV size and anterior wall thickness tended to decrease, and RV diastolic function - to improve. Therefore, Cardilopin could be used for pharmaceutical correction of pulmonary hypertension and morpho-functional RV abnormalities in patients with severe thoracic scoliosis.